INVESTIGATION OF THE ANTIBACTERIAL ACTIVITY OF PSORALEA CORYLIFOLIA LEAF AND CALLUS EXTRACTS AGAINST MULTIDRUG RESISTANT PERIODONTAL DISEASE CAUSING MICROORGANISMS: Life Science-Microbiology - MOON, ARCHANA; MOON, NINAD (International Journal of Life Science and Pharma Research, 2012)
Some specific microorganisms have been identified as etiologic agents of periodontitis. The main goal of treatment is to control the spread of infection. Depending on the extent of the gum disease, treatment varies. Therapeutic antibiotic along with surgery are the most opted form of treatment. But, due to high costs of antibiotics, the disastrous side effects and emergence of multi drug resistant strains of the pathogenic bacteria, a safe alternative is being investigated scientifically in this study. The in vitro antibacterial activity of Psoralea corylifolia leaf and its corresponding callus extracts were studied against pathogenic bacteria causing periodontitis. Leaves and corresponding calli were extracted using petroleum ether, chloroform, acetone, methanol and distilled water. Among the five solvents used, leaf and callus extracted in methanol were found to be more effective against pathogenic bacteria. Psoralea corylifolia extracts should be further studied to determine the bioactive compounds as well as to understand the possible mechanisms of action and evaluate its toxicity looking towards a pharmaceutical employment.